Levantamento e classificação de resíduos de construção e demolição em Ilha Solteira-SP - Oliveira, Cássio Eduardo Martins de [UNESP] (2014)
The rural exodus is defined as a population migration from rural to urban areas seeking an improved quality of life, causing the search for habitat close to labor camps to meet their daily needs, but contributing to the deterioration of quality of life denominated in the settlements. In Brazil, the process of rural exodus had an enormous increase from 1950, bringing the process of urbanization and the rise of civil constructions, there by generating a very large amount of waste Construction (RCC). The main objective of this research was to conduct a survey and classification of Construction and Demolition Waste (RCD) in the municipality of Single Island - SP, collecting data, estimating local dumps, assessing impacts and suggesting a management proposal for such waste. Through permits issued by the municipal government and the motion of the charge collecting agents, registered an average generation of RCD of 45 tons per day, approximately 25 ton / day for renovations / demolitions and 21,5 ton / day for new works. This view, the present work aims to contribute to an efficient management of RCC, with effective actions from specific knowledge of the city under study